Stanley the impossible life of Africa's greatest explorer - Jeal, Tim (Faber, 2008)
Henry Morton Stanley was a cruel imperialist, who connived with King Leopold II of Belgium in horrific crimes against the people of the Congo - or so we think. Tim Jeal shows that this perception is not true. Now, abundant new documentary evidence allows Jeal to show just how misunderstood Stanley's life has been.